Operational risk perspectives : cyber, big data, and emerging risks - Maurice, D. R.; Rathod, Jitendra (London: Risk books, 2016)
Operational risk perspectives covers key topics related to operational risk currently on the minds of practitioners. The book provides an overview of the current state of this discipline and the top operational risk concerns at the forefront of the industry.
Includes index
nmn 08/01/19, ijb,28/01/2019
Loans
Keywords: Financial risk management; Operational risk; Cyber security; Emerging risk; Operational risk management